La responsabilité des agences de voyages : les tendances de la jurisprudence récente - Rousseau-Houle, Thérèse (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
A travel agent's liability normally differs according to whether he merely acts as a middleman between clients and service suppliers or whether he himself organizes travel. Court decisions reveal nevertheless that proper qualification of the relationship is not necessarily a prerequisite as to the rules applicable. The overriding criterion appears rather to be consumer protection. Consequently, the burden of proof on the consumer has been slightly reduced and travel agents are more often than not held liable under an obligation of result.